2021
DOI: 10.18016/ksutarimdoga.vi.868927
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of antioxidant, cytotoxic, and anti-inflammatory activities of different Cladonia species and determination of fumarprotocetraric acid amounts

Abstract: The study aimed to determine the biological activities of 70% methanol extracts of nine Cladonia species from Turkey. The chemical composition was analyzed via spectrophotometric and chromatographic (HPLC) techniques. DPPH • (1,1-diphenyl-2picrylhydrazyl) and ABTS +• (2,2'-azino-bis (3-ethylbenzothiazoline-6sulphonic acid) radical scavenging activities, inhibition of βcarotene/linoleic acid co-oxidation, and cytotoxicity on A549 and COLO205 cell lines were studied. Anti-inflammatory activity was assessed on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Previously, Mendili et al 20 showed that acetone extract of Tunisian lichen C. rangiformis had DPPH antioxidant capacity (IC 50 = 23.0 μg/mL). Kocakaya et al 21 found ABTS radical removal effect of the methanolic extract of C. rangiformis (2.50 mmol/L/Trolox). According to previous research, there is no data for the analysis of the ability of C. rangiformis acetone extract to neutralize ABTS radicals.…”
Section: Tpc and Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Mendili et al 20 showed that acetone extract of Tunisian lichen C. rangiformis had DPPH antioxidant capacity (IC 50 = 23.0 μg/mL). Kocakaya et al 21 found ABTS radical removal effect of the methanolic extract of C. rangiformis (2.50 mmol/L/Trolox). According to previous research, there is no data for the analysis of the ability of C. rangiformis acetone extract to neutralize ABTS radicals.…”
Section: Tpc and Antioxidant Activitymentioning
confidence: 99%
“…19 The studies of the radical scavenging ability and reducing power capacity on the Tunisian lichen C. rangiformis acetone extract showed that it possesses antioxidant activity. 20 Kocakaya et al 21 found ABTS radical removal effect of the C. rangiformis methanolic extract.…”
Section: Introductionmentioning
confidence: 99%